Pemanfaatan Situs Kota Cina Sebagai Sumber Belajar Sejarah di Madrasah Aliyah Tahfizhil Qur’an - Idris Memori Simamora; Sipriana A Sihaloho; Even Susantri Pakpahan; Kevin Winner Sitorus (Program Studi Pendidikan Biologi, 2022)
History learning according to its function is to make students aware of the process of change and development of society in the dimension of time and to build historical perspectives and awareness in discovering, understanding and explaining the identity of the nation in the past, present, and future. The role of the teacher as a facilitator in learning does not seem to have developed widely, with the application of the lecture method, the role of the teacher leads to a single source of information, teaching and communication only goes one way so that it does not provide opportunities for students to think critically analytically and dialogical teaching is difficult to realize. This research using qualitative descriptive research methods with a research location in Madrasah Aliyah Tahfizhil Qur'an. The main subject of this study is the history teacher at the Madrasah Aliyah Tahfizhil Qur'an who teaches focusing on learning activities about the historical material hindhu – Buddha. To support the learning process of history, teachers design learning designs that are integrated with Hindu Buddhist history learning materials, community life and heritage sites. Learning history by utilizing chinese city sites has a positive influence on students' knowledge, behavior and creativity. In addition to gaining knowledge and understanding of the history of hindhu Buddha development on the island of Sumatra, the state of society and the heritage sites of the city of trying to be critical, students are also able to implement the values contained in the historical material of Hindhu Buddha, namely an attitude of tolerance, help, being kind to people of different ethnicities and beliefs as well as an attitude of love for the homeland.